Protéger les sols et lutter contre le changement climatique : comment mesurer les disparités de stratégies locales ? - Éric Perret; Éric Cahuzac; Pierre Cantelaube; Nadia Guiffant; Nadine Turpin (VertigO, 2015)
Protection of soil quality and adoption of practices that could mitigate climate change strongly depends on both farm types and soils threats at local level, but there has been so far no general analysis in France of what combinations are used and where. This paper uses information aggregated from the FADN database and combines it with threats on soils to build a typology of LAU1 French territories regarding their soil protection strategies. We highlight four main paths : some territories rely on the sets of “good practices” designed from action programs from the Nitrate Directive, and those only. Others have developed interesting combinations of conservation tillage, cover crops and agri-environmental schemes. Some have chosen to combine reduced use of fertilisers and pesticides and the last ones happen to show no obvious protection strategy.